2002
DOI: 10.1002/ca.10066
|View full text |Cite
|
Sign up to set email alerts
|

Extensive somatosensory innervation in infants with obstetric brachial palsy

Abstract: In the pre-operative screening of infants with obstetric brachial palsy (OBP), the results of routine electromyography are often overly optimistic when compared to the peri-operative findings. This prompted us to include investigation of the sensory innervation of these infants using the N20 (the first cortical response to a peripheral stimulation) of the somatosensory evoked potentials (SSEP). Three to seven months after birth, SSEP were recorded at the skull after stimulation of the thumb and middle finger i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Our findings agree with Colon et al. : 25 there is reasonably good sensation in skin areas in which profound deficits might be expected. The absence of such major ‘gaps’ in sensation in OBPL may be explained partly by the fact that in most infants with OBPL there is no anatomical gap between two torn nerve stumps.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings agree with Colon et al. : 25 there is reasonably good sensation in skin areas in which profound deficits might be expected. The absence of such major ‘gaps’ in sensation in OBPL may be explained partly by the fact that in most infants with OBPL there is no anatomical gap between two torn nerve stumps.…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation is that the dermatomes overlap extensively; so, many adjacent spinal levels should be compromised in order to generate a sensory deficit 19 . Collon et al also suggested the possibility of alternative paths for peripheral sensory information in young infants with brachial plexus lesions 20 . One very tempting explanation is related to the physiopathology of neurapraxia 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, imaging had a specificity of 29.4% at C8 and 57.1% at T1. Finally, the use of preoperative SEP showed no value in determining severity of the plexus lesion as it may be confounded by the persistence of the fetal polyneuronal innervation of the somatosensory system in children with NBPP …”
Section: Discussionmentioning
confidence: 99%